A new approach to understanding the Abu Ghraib prison torture scandal. (13th September 2010) - Winton, Mark A.; Unlu, Ali
The purpose of this study is to examine a method of predicting and understanding torture during international conflicts by applying and linking two established theoretical approaches to the Abu Ghraib case. The first theoretical approach is based on the circumplex model of family functioning focusing on cohesion, flexibility, and communication (Olson, 1995, 2000; Olson and DeFrain, 1997). In this model, social groups at the extreme points on the flexibility and cohesion dimensions have the highest level of risk for violence. The second approach is based on violentisation theory (Athens, 2003). The four stages of the violentisation process include: brutalisation, defiance, violent dominant engagements, and virulency. Extreme virulency was added as another stage. Using qualitative content analysis, the data demonstrated that the perpetrators moved through the violentisation process as their social environment moved toward the chaotic and disengaged extremes of the circumplex model. Study limitations and suggestions for further research are also addressed.